Infrasound detection and altitude estimation associated with the December 22, 2020 Yushu fireball - Wei Cheng; Pengxiao Teng; Jun Lyu; Yijing Dai (Geoscience Letters, 2021)
Abstract A large bolide was reported at 23:23:33 UTC on December 22, 2020, at a height of ~ 35.5 km at $$31.9^° N$$ 31 . 9 ∘ N , $$96.2^° E$$ 96 . 2 ∘ E in Yushu, Qinghai Province, China. It is the largest fireball observed in China on record with a TNT equivalent of 9.5 kilotons. Infrasound signals were detected by a four-element infrasound array deployed in Yunnan Province, China. The parameters of this event were obtained using the progressive multi-channel correlation method. The altitude of this event was estimated to be $$43.22± 15.51 km$$ 43.22 ± 15.51 km using a ray tracing back-projection algorithm.